Loss of Myeloid BMPR1a Alters Differentiation and Reduces Mouse Prostate Cancer Growth - Ihle, Claire L.; Straign, Desiree M.; Provera, Meredith D.; Novitskiy, Sergey V.; Owens, Philip (Frontiers in Oncology, 2020)
The Bone Morphogenetic Protein (BMP) pathway is a member of the TGFB signaling family and has complex roles in cancer. BMP signaling is rarely mutated and can be frequently overexpressed in many human cancers. The dichotomous role of BMPs as both tumor promoters and suppressors appears to be largely context based in both the cancer cell and the surrounding microenvironment. Myeloid cells including macrophages and neutrophils have been shown to be tumor promoting when stimulated from BMPs. We found that conditional deletion of BMPR1a in myeloid cells (LysMCre) restricts tumor progression in a syngeneic mouse prostate cancer model. Specific changes occurred in myeloid cells both in tumor bearing mice and tumor naïve mice throughout multiple tissues. We profiled myeloid subsets in the bone marrow, spleen and primary tumor and found myeloid BMPR1a loss altered the differentiation and lineage capability of distinct populations by histologic, flow cytometry and high dimensional mass cytometry analysis. We further confirmed the requirement for BMP signaling with pharmacologic inhibition of THP-1 and Raw264.7 activated into M2 macrophages with the BMP inhibitor DMH1. M2 polarized primary bone marrow derived cells from LysMCre BMPR1a knockout mice indicated a distinct requirement for BMP signaling in myeloid cells during M2 activation. These results indicate a unique necessity for BMP signaling in myeloid cells during tumor progression.